Giving Various Concentrations of Mangosteen Peel Extract by Spraying Method to Rice Quality in Perum Bulog, Cianjur Regional Subdivision - Suhartono; Nurani; Risdayanti (PT FORMOSA CENDEKIA GLOBAL, 2023)
As the main food commodity in Indonesia, the quality of rice is an important thing that must be considered, including postharvest handling during storage. Improper storage conditions can trigger pest and microbial contamination which has the potential to accelerate rice quality degradation during storage. Mangosteen peel is rich in antimicrobial and antifungal compounds, but their use is still limited. This study aims to determine the effect of mangosteen peel extract at concentrations of 2.5%, 5%, and 7.5% on the quality of rice in the medium class category for 30 days of storage at the Cianjur regional sub-division BULOG warehouse. The results show that the decline in the quality of rice including moisture content, broken kernel, chips, yellow kernel and the presence of pests could not be slowed down by administering mangosteen peel extract. Until the end of the storage period, Ahasverus advena was the most commonly found pest. The percentage of water content, broken grains, groats, and yellow grains in rice at the end of storage in all treatments can still be categorized into the medium class according to SNI with an average value of respectively 12.53%, 13.36 %, 4.02%, and 1.27%.